Clinical Relevance of Isolated Lupus Anticoagulant Positivity in Patients with Thrombotic Antiphospholipid Syndrome - Yin, Dongmei; de Groot, Philip G.; Ninivaggi, Marisa; Devreese, Katrien M. J.; de Laat, Bas (Thrombosis and Haemostasis, 2021)
Background Patients positive for all three types of antiphospholipid antibodies (aPLs; triple positivity) have been identified for having a high risk for thrombotic events. However, the clinical significance of isolated lupus anticoagulant (LAC) positivity is debated.Objectives To investigate the clinical relevance of isolated LAC.Methods A total of 456 patients were enrolled in this study; 66 antiphospholipid syndrome patients and 390 control patients. The control group consisted of autoimmune patients (n = 91), patients with thrombosis but without aPLs (n = 127), and normal controls (n = 172). LAC, anticardiolipin (anti-CL), and anti-β2 glycoprotein I (anti-β2GPI) immunoglobulin G (IgG) and immunoglobulin M (IgM) were determined according to the International Society on Thrombosis and Haemostasis (ISTH) guidelines. Anti-CL and anti-β2GPI were measured by four different solid-phase platforms to overcome variability between test systems. The noncriteria IgA anti-CL and anti-β2GPI, antidomain I of β2GPI IgG, and antiphosphatidylserine/prothrombin antibodies (anti-PS/PT) IgG and IgM were detected according to the ISTH guidelines for solid-phase assays.Results In total, 70 patients were positive for LAC, of which 44 were negative for both anti-β2GPI and anti-CL antibodies. We found that isolated LAC proved to be strongly associated with vascular thrombosis (odds ratio [OR]: 7.3; 95% confidence interval [CI]: 3.3–16.1), even better than triple-positive samples (OR: 4.3; 95% CI: 1.6–12.2). The titers of the anti-PS/PT IgG and IgM were significantly higher in triple-positivity samples compared with samples with isolated LAC positivity. The majority of single LAC positives were anti-PS/PT-negative. We observed that LAC positivity was weaker in isolated LAC-positive patients compared with LAC activity in triple-positive patients.Conclusion Isolated LAC was highly associated with thrombosis. The presence of anti-PS/PT antibodies could not explain LAC positivity in isolated LAC. Isolated LAC showed a weaker LAC activity compared with triple-positive patients.
Keywords: antiphospholipid antibodies; β2 glycoprotein I; lupus anticoagulant; prothrombin; thrombosis